Analisis Pengaruh Sistem Informasi Akuntansi dan Motivasi Kerja Terhadap Efektivitas Kinerja (Studi Kasus Pada Karyawan CV. Algostudio) - Bilah, Tasya Salsa; Maslichah, Maslichah; Mawardi, M. Cholid (Universitas Islam Malang, 2024)
This research aims to investigate the impact of the Accounting Information System and Work Motivation on Performance Effectiveness. This investigation employs a quantitative methodology, targeting the staff of CV. Algostudio as the population. The study included 40 respondents, selected through a saturated sampling method. In this investigation, the analysis of the data was conducted using multiple linear regression. The analysis executed using SPSS version 29 indicates that both the Accounting Information System and Work Motivation contribute significantly and positively to Performance Effectiveness when assessed collectively. It was observed that individually, the Accounting Information System does not influence Performance Effectiveness, whereas Work Motivation individually exerts a notable positive impact on Performance Effectiveness.Keywords: Performance Effectiveness, Accounting Information System, Work Motivation.